‘A Garland in Place of Ashes’:Transformative Spirituality and Mission in the Post-Modern and Secular Contexts - Cruchley-Jones, Peter (International review of mission, 2009)
In this paper I aim to explore not what is the so-called ‘post-modern and secular context’ but how the church responds to it, which is predominantly to blame it for ‘decline’. Yet it may not be decline, it may be something else altogether. I am reflecting on a western/UK context, but within this are theological assumptions that characterize the wider church. So, having made some remarks on how to approach decline I will then explore some transformations of spirituality and mission that are responses to the post-modern and secular context. Underlying this is an attitude to ‘spirituality’ which is not about how we worship or our experience of the ‘ethereal’ but is about our ‘capacity for life’. But, I want to maintain that nothing new or transformative can emerge until the church stops resenting and despairing of the context and change we are experiencing. Further, I am not convinced the church in the UK or the West is able to adapt to the strangeness of this new context and will seek always to bring it back under church control. But, I will then offer a post-modern image for transformative spirituality and mission that could leave its mark on the church.